Recent Advances in the Use of the SNAP-tag® in the Modern Biotechnology - Merlo, Rosa; Mattossovich, Rosanna; Valenti, Anna; Perugino, Giuseppe (Recent Research Advances in Biology Vol. 7, 2021)
Alkylguanine-DNA-alkyltransferases (AGTs) have a natural role in the protection of DNA from mutations caused by alkylating agents. Their peculiar irreversible self-alkylation reaction led to the development as new tools in the modern biotechnology. SNAP-tag® is a powerful enzyme for the specific labelling of protein/enzymes by using benzyl-guanine (BG) derivatives as substrates. This technology has some limitations, as the mesophilic nature of the tag (an engineered variant of the human enzyme) and the needs of purify each substrate. Recently, the SNAP-tag® technology was successfully implemented by the employment of thermostable “SNAP-tag-like” variants from (hyper)thermophilic sources, and by the utilization of BG-substrates containing an azide group to be combined with DBCO-derivatives by azide-alkyne Huisgen cycloaddition. The introduction of these new actors on the scene made possible the expansion of the methodology to in vivo and in vitro harsh reaction conditions, as well as the utilization of more chemical groups in the overall reaction enzyme labelling.